18F‐FDG uptake in denervated muscles of patients with peripheral nerve injury. Issue 11 (6th October 2019) - Choi, Ji Soo; Seo, Han Gil; Oh, Byung‐Mo; Choi, Hongyoon; Cheon, Gi Jeong; Lee, Shi‐Uk; Lee, Seung Hak
Abstract: Objective: We aimed to investigate the clinical significance of increased uptake in 18 F‐fluorodeoxyglucose positron emission tomography in patients with peripheral nerve lesions. Methods: We selected patients with unilateral peripheral nerve lesions confirmed with electromyography who had undergone 18 F‐fluorodeoxyglucose positron emission tomography covering the lesions. In the denervated muscles and their contralateral corresponding pairs, a mean (SUVmean) and maximum standardized uptake value (SUVmax) were obtained from 18 F‐fluorodeoxyglucose positron emission tomography images. We analyzed the difference in these values between the denervated and normal muscles. The lesion‐to‐normal ratio of the SUVmean (LNRmean) between each muscle pair was also obtained. Subgroup analysis was performed to find whether these three parameters were related to severity, abundance of abnormal spontaneous activity, and etiology. Results: Twenty‐three patients with 38 denervated muscles were included. Compared to their normal counterparts, the denervated muscles showed significantly higher SUVmax (1.33 ± 0.49 vs. 1.10 ± 0.37, n = 38, P < 0.001) and SUVmean (0.91 ± 0.31 vs. 0.77 ± 0.28, n = 38, P < 0.001). The muscles with severe neuropathy showed significantly higher LNRmean than those with mild neuropathy (1.30 ± 0.36, n = 19 vs. 1.11 ± 0.24, n = 19; P = 0.046), and the muscles with traumatic neuropathy showed significantly higher LNRmean than those with nontraumatic neuropathy (1.32 ± 0.28, n = 13 vs. 1.14 ± 0.33, n = 23; P = 0.015). Interpretation: Denervated muscles with peripheral nerve injury showed higher uptake than normal muscles in 18 F‐fluorodeoxyglucose positron emission tomography, and this was associated with severity and etiology.